Validated RP-TLC Method with Densitometry for Assay of Finasteride in Simple Pharmaceutical Dosage Form - Dolowy, Malgorzata; Piontek, Agata; Pyka-Pajak, Alina (Current Pharmaceutical Analysis, 2018)
Background: Finasteride is a medically important compound belonging to 4-azasteroids which are widely used in the treatment of benign prostatic hypertrophy. Therefore, there is a need to find a simple, cost effective and sensitive method for the determination of finasteride in commercially available tablet dosage form. Objective: To develop and validate a rapid and simple RP-TLC method combined with densitometry for the quantification of finasteride in tablet dosage form containing 5 mg of active substance alone. Method: Chromatographic analysis was performed on aluminum plates precoated with silica gel 60 RP18F254 using mobile phase consisting of 1,4-dioxane-water in volume composition 35:15. Densitometric scanning was done in the absorbance mode at 212 nm. Validation of proposed RP-TLC method was carried out according to the ICH guidelines. Results: Validation data indicated that the proposed RP-TLC method was accurate and precise with coefficient of variation CV, to be less than 2% in both cases. The method was linear over the range of 1.00÷4.00 μg/spot with correlation coefficient equal to 0.9981. The LOD and LOQ were found to be 0.24 and 0.74 μg/spot, respectively. Assay results of finasteride in marketed tablets using this method were in agreement with label claim and also with pharmacopoeial requirements. Conclusion: A new, simple and economical RP-TLC method with densitometry developed in this study can be found to be suitable for routine analysis of finasteride in simple tablet dosage form containing this active substance.
Keywords: chromatography